(untitled) (Bulletin of the Department of Geology, 2011)
Geological study was carried out along the Pasang Lahmu Highway from Kathmandu to Trishuli Bazaar covering both theLesser Himalayan autochthonous unit and the Kathmandu Nappe. The Lesser Himalayan rocks in the study area belong to theKunchha Formation, Benighat Slate and the Robang Formation of the Nawakot Complex. The Kathmandu Nappe (KathmanduComplex) comprises the Kalitar Formation, Gneiss Zone, Tistung Formation, Sopyang Formation and the Chandragiri Limestone.Petrographic study was carried out in the samples representing all the lithological units along the Pasang-Lahmu Highway.The study shows that the Kunchha Formation belongs to the biotite zone. The overlying units (Benighat Slate and RobangFormations) belong to the garnet zone. It is a clear evidence of inverted metamorphic zonation at the foot wall of the KathmanduNappe. The rocks of the Kathmandu Complex above the Mahabharat Thrust north of Kakani also show an inverse metamorphiczonation, i.e., the garnet zone is overlain by the sillimanite zone. However, in the southern part, the metamorphic zonation isnormal with biotite zone overlain by the chlorite zone. Although the inverted metamorphic zonation at the hanging wall of theMahabharat Thrust may be related to the high temperature contact metamorphism by pegmatite injection, the inverted metamorphismat the footwall needs an explanation. DOI: http://dx.doi.org/10.3126/bdg.v14i0.5439 Bulletin of the Department of Geology, Vol. 14, 2011 pp. 51–58